1987
DOI: 10.1128/mcb.7.9.3361
|View full text |Cite
|
Sign up to set email alerts
|

Control of hematopoietic cell growth regulators during mouse fetal development.

Abstract: Gene expression for the four different growth-regulatory proteins for cells of the myeloid hematopoietic cell lineages was analyzed in mouse fetal and extraembryonic tissues at various stages of development. The macrophage growth inducer MGI-1M (colony-stimulating factor 1) was the only myeloid hematopoietic growth regulator detected as both mRNA and bioactive protein during fetal development. This regulator was produced predominantly in extraembryonic tissues, and the production of hematopoietic growth regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 33 publications
4
11
0
Order By: Relevance
“…CSF-1 is also found in placenta, amniotic fluid, and at low concentrations in the fetus (5,20,21). CSF-1 mRNA is restricted to the luminal and glandular epithelium throughout pregnancy, indicating that the CSF-1 detected in the placenta and amniotic fluid is synthesized in the uterus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CSF-1 is also found in placenta, amniotic fluid, and at low concentrations in the fetus (5,20,21). CSF-1 mRNA is restricted to the luminal and glandular epithelium throughout pregnancy, indicating that the CSF-1 detected in the placenta and amniotic fluid is synthesized in the uterus.…”
Section: Discussionmentioning
confidence: 99%
“…While CSF-1 mRNA has been detected in placental samples by Northern blotting (6,20), both in situ studies failed to detect significant placental CSF-1 mRNA. This suggests that the detection of "placental" CSF-1 mRNA by Northern blotting was due to uterine contamination of placental samples.…”
mentioning
confidence: 98%
“…Daiter et al [12] and Saito et al [13] reported similar findings. In contrast to M-CSF, CA 125 reaches high levels among pregnant women, espe cially in the first trimester [8,14,15], Azoulay et al [16] reported that M-CSF is produced in the placenta and embryonic membrane of mice. Pollard et al [17] reported that it is produced in the uterine glandular epithelium of mice.…”
Section: Discussionmentioning
confidence: 99%
“…Besides hematopoiesis, the secondary yolk sac is an active site of protein biosynthesis and nutrient transport [90,94]. The endodermal component of the primate secondary yolk sac is a known transporter of proteins and vitamins [95][96][97].…”
Section: Yolk-sac Formation Differs In Man and Mousementioning
confidence: 99%